1991
DOI: 10.1210/jcem-72-4-779
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor Binding Proteins in Human Endometrium: Steroid-Dependent Messenger Ribonucleic Acid Expression and Protein Synthesis*

Abstract: The insulin-like growth factor (IGF) autocrine/paracrine system is believed to play a role in endometrial differentiation and trophoblast growth. The IGFs bind with high affinity to a family of binding proteins (IGFBPs) that regulate the actions of the IGFs at their target cells. IGFBP-1, one of three well-characterized IGFBPs in humans, has been shown by numerous investigators to be present in secretory but not proliferative endometrium; however, no information is available with regard to two other human IGFB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(36 citation statements)
references
References 65 publications
1
35
0
Order By: Relevance
“…Significant uterine endometrial IGFBP-2 expression has been demonstrated for a number of mammals (Giudice et al 1991, Rechler 1993 et , Cerro & Pintar 1997. In porcine uterus, this expression is induced during the periimplantation period and reaches maximal levels by mid-pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant uterine endometrial IGFBP-2 expression has been demonstrated for a number of mammals (Giudice et al 1991, Rechler 1993 et , Cerro & Pintar 1997. In porcine uterus, this expression is induced during the periimplantation period and reaches maximal levels by mid-pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Although the complete mechanism(s) of action has not been fully defined for any of the IGFBPs, these proteins can augment or inhibit IGF action, depending upon the nature of the IGFBP, the cell context and the experimental conditions. Uterine endometrial expression of IGFBP-2 has been demonstrated in the human (Giudice et al 1991), pig (Simmen et al 1992, Song et al 1996, and rat (Cerro & Pintar 1997), in addition to other species. In pregnant pig uterus, the abundance of IGFBP-2 mRNA and protein is induced during late pre-implantation (around day 15, postestrus) and reaches maximal levels by mid-pregnancy (day 60) (Simmen et al 1992, Song et al 1996.…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, IGFBP-2, -4, -5 and -6 mRNAs demonstrate a diffuse stromal pattern of expression, whereas IGFBP-1 and -3 are more concentrated in selected subpopulations of endometrial cells , Zhou et al 1994. IGFBP-2 and IGFBP-3 mRNAs are significantly increased in the late secretory phase of the endometrium (Giudice et al 1991). Moreover, IGFBP-3 mRNA is primarily concentrated in endometrial capillaries, largely due to the intensive vascularization of endometrial glands during the secretory phase (Zhou et al 1994).…”
Section: Regulation Of Proliferation and Differentiation In The Endommentioning
confidence: 95%
“…Expression of mRNA encoding IGFBP-2 and -3 in human endometrium (Giudice et al, 1991) and secretion of multiple forms of IGFBPs by decidual cells (Clemmons et al, 1990) Insulin-like growth factor binding proteins in the uterine extracts and serum were analysed by western ligand blotting (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%